1990
DOI: 10.1002/ijc.2910460403
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cigarette smoking on the levels of DNA adducts in human bronchial epithelium and white blood cells

Abstract: The presence of carcinogen-DNA adducts in human tissues is evidence of exposure to carcinogens and may be an indicator of cancer risk. DNA was isolated from non-tumorous bronchial tissue of 37 cigarette smokers, 8 former smokers and 8 non-smokers and analyzed for the presence of aromatic andlor hydrophobic DNA adducts in the 32P-post-labelling as-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
3

Year Published

1991
1991
2004
2004

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(56 citation statements)
references
References 48 publications
4
49
3
Order By: Relevance
“…Some studies have found a linear correlation between adduct levels and daily or lifetime consumption of cigarettes (Phillips et al, 1988(Phillips et al, , 1990Dunn et al, 1991). Similar linear relationship was also found in bladder cancer biopsies.…”
Section: Dna Damage and Repairsupporting
confidence: 53%
“…Some studies have found a linear correlation between adduct levels and daily or lifetime consumption of cigarettes (Phillips et al, 1988(Phillips et al, , 1990Dunn et al, 1991). Similar linear relationship was also found in bladder cancer biopsies.…”
Section: Dna Damage and Repairsupporting
confidence: 53%
“…A consistent finding is that levels of aromatic and hydrophobic adducts are significantly higher in smokers than in nonsmokers (9)(10)(11)(12)(13). In some studies, a linear correlation between estimated total or daily tobacco smoke exposure and adduct levels has been observed.…”
Section: Smoking-related Dna Adducts In Human Tissuesmentioning
confidence: 77%
“…Studies on smokers and nonsmokers showed conflicting results on the effect of smoking on PAH-DNA adduct levels in WBC. Several studies did not reveal any significant differences in PAH-DNA adduct levels between the two groups Phillips et al, 1990;Van Maanen et al, 1994a), suggesting that adducts in WBC may result from other sources than tobacco smoking. In a study among roofers, PAH-DNA adduct levels in WBC correlated with the amount of PAH in skin wipes, but not with the amount of PAH in personal air samples, indicating that dermal contact might be a major route for DNA adduct formation in WBC (Herbert et al, 1990).…”
Section: Studies In Humansmentioning
confidence: 95%